Architectural design communication (ADC) in online education during COVID-19 pandemic: a comparison of Turkish and Spanish universitie - Akçay Kavakoğlu A.; Güleç Özer D.; Domingo-Callabuig D.; Bilen, Ömer (Emerald Group Holdings Ltd., 2022)
Purpose: The paper aims to examine the concept of architectural design communication (ADC) for updating design studio dynamics in architectural education during the Covid-19 pandemic. Within this perspective, the changing and transforming contents of architectural education, the thinking, representation and production mediums are examined through the determined components of ADC. There are five components in the study, which are (1) Effective Language Use, (2) Effective use of Handcrafts, (3) Effective Technical Drawing Knowledge, (4) Effective Architectural Software Knowledge and (5) Outputs. Design/methodology/approach: The research method is based on qualitative and quantitative methods; a survey study is applied and the comparative results are evaluated with the path analysis method. The students in the Department of Architecture of two universities have been selected as the target audience. Case study 1 survey is applied to Altinbas University (AU) and Case study 2 survey is applied to Universitat Politecnica de Valencia (UPV) students during the COVID-19 pandemic; ‘19-‘20 spring term, online education. Findings: As a result, two-path analysis diagrams are produced for two universities, and a comparative analysis is presented to reveal the relationships of the selected ADC components. Originality/value: This paper fulfills an identified need to study how ADC can be developed in online education platforms.

Architectural design communication (ADC)
Keywords: Architectural design education; Architectural design communication (ADC); Communication; COVID-19 pandemic; Design studio; Path analysis